The Melatonin Receptor Agonist Ramelteon Effectively Treats Insomnia and Behavioral Symptoms in Autistic Disorder - Kentaro Kawabe; Fumie Horiuchi; Yasunori Oka; Shu-ichi Ueno (Case Reports in Psychiatry)
Children with autism spectrum disorders (ASD), including autistic disorder, frequently suffer from comorbid sleep problems. An altered melatonin rhythm is considered to underlie the impairment in sleep onset and maintenance in ASD. We report three cases with autistic disorder in whom nocturnal symptoms improved with ramelteon, a selective melatonin receptor agonist. Insomnia and behavior, assessed using the Clinical Global Impression-Improvement Scale, improved in two cases with 2 mg ramelteon and in the third case with 8 mg ramelteon. Our findings demonstrate that ramelteon is effective not only for insomnia, but for behavioral problems as well, in patients with autistic disorder.